Assessment purposes and methods used by EFL teachers in secondary schools in Jordan - Swaie, Malak; Algazo, Muath (Frontiers in Education, 2023)
This study examines the purposes and methods of classroom-based assessment (CBA) used by English as a Foreign Language (EFL) teachers in secondary schools in Jordan. The study data was collected through an online questionnaire that surveyed 54 participants and follow-up semi-structured interviews with 3 teachers. The questionnaire data were analyzed in SPSS using descriptive statistics, while the interviews were transcribed and coded for recurrent themes. The data showed that teachers use assessment to achieve various goals, including those related to students' performance, instruction, and administration. The study also found that teachers employed a range of assessment methods of which teacher-made tests was the most common. Additionally, teachers' choices of assessment methods were found to be influenced by factors such as the National Exam (Tawjihi), students' proficiency level, as well as their own knowledge of assessment. These findings have implications for prompting awareness among EFL stakeholders in Jordan about the vital role of CBA and the necessity to improve teacher training and professional development programs in order to enhance teachers' assessment knowledge and practices.